Toward synthetic learning across the CCAFS Flagship on Climate Services and Safety Nets - Vaughan, Catherine; Rose, Alison; Zebiak, Stephen E. (2019)
Immediately prior to the 5th Global Science Conference on Climate-Smart Agriculture 2019, held in Bali, Indonesia, the team responsible for Flagship 4 gathered the diverse group of scientists and practitioners responsible for the portfolio of projects together in order to explore avenues to produce synthetic learning across the Flagship. The goal of the activity was to brainstorm about common challenges, experiences, and insights, and to create opportunities for world-class scientists that comprise the Flagship to work together to distil key learning and thus advance the field of agricultural climate services.